Mr Steer. Bilbao : inter-departmental correspondence - Gillies, William
028-0066-001 TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From: W. Gillies. To: Sir Walter Citrine. Department: International. Date: February 5, 1937. SUBJECT. Mr. STEER BILBAO. Mr. Steer, whom I met at your request, was the former "Times" correspondent in Abyssinia, and the "Times" correspondent with Franco. He was expelled by Franco as the result of an Italian report on his activities in Abyssinia. He left Bilbao last week end. He will be writing articles in the "Times" on the situation in the Basque country. His report on the situation is very good. Order is being maintained by the police and radio communications. The Anarchists are kept well in hand, and military and hospital organisation are good. They lack medical supplies. There was heavy fighting in December and January, when there were 700 people killed. Whilst in Bilbao he met Madam MALLATERO SELLIER, French delegate to the League of Nations (I think she is the wife of Sellier of the French Socialist Party). She said that the food position in Bilbao was worse than in any part of Spain. The military hospitals are fairly well supplied with food, but the civil population are entirely lacking milk for the children. There is hardly any soap, and a good deal of typhoid exists. Meat is almost impossible to obtain, and there are no cattle. Horses have been killed off, horse flesh has disappeared. Bread is rationed, and even then there is only black bread to be had, and that is getting scarce. Beans also are getting scarce, and potatoes are almost impossible to obtain. There is no wine, but it is not considered that this is a necessity. The people are living on fish and bread. Sugar will be cut off very soon. Last week end it was said that they had sufficient bread, beans and sugar to last for three weeks. Mr. Spier said that the spirit of the people is very good. They are a good and moderate type, and if food could be supplied to them, very probably an offensive could be launched from that quarter. The point that has been emphasised throughout the interview is that food and milk are necessary for the children. EAB/AC/397. 292/946/28/66